POLLUTION OF SOILS OF INDUSTRIAL TERRITORIES AND WAYS OF THEIR EFFICIENT CLEANING - Jobborov Baxrom Turg‘unovich; Xayrullayeva Durdona; Zaxirova Dilora (Лучшие интеллектуальные исследования, 2023)
Annotation: The article provides information on soil pollution of the industrial zone as a result of heavy metal emissions. Methods of technical and biological reclamation of polluted soils have also been studied.